Exposure to Cigarette Smoke Enhances Pneumococcal Transmission Among Littermates in an Infant Mouse Model - Murakami, Daichi; Kono, Masamitsu; Nanushaj, Denisa; Kaneko, Fumie; Zangari, Tonia; Muragaki, Yasuteru; Weiser, Jeffrey N.; Hotomi, Muneki (Frontiers in Cellular and Infection Microbiology, 2021)
Streptococcus pneumoniae, one of the most common commensal pathogens among children, is spread by close contact in daycare centers or within a family. Host innate immune responses and bacterial virulence factors promote pneumococcal transmission. However, investigations into the effects of environmental factors on transmission have been limited. Passive smoking, a great concern for children’s health, has been reported to exacerbate pneumococcal diseases. Here, we describe the effect of cigarette smoke exposure on an infant mouse model of pneumococcal transmission. Our findings reveal that the effect of cigarette smoke exposure significantly promotes pneumococcal transmission by enhancing bacterial shedding from the colonized host and by increasing susceptibility to pneumococcal colonization in the new host, both of which are critical steps of transmission. Local inflammation, followed by mucosal changes (such as mucus hypersecretion and disruption of the mucosal barrier), are important underlying mechanisms for promotion of transmission by smoke exposure. These effects were attributable to the constituents of cigarette smoke rather than smoke itself. These findings provide the first experimental evidence of the impact of environmental factors on pneumococcal transmission and the mechanism of pathogenesis.